Who Were the Women? In-Depth Analysis of Four Additional Early Women Adult Educators - Susan Imel; Gretchen T. Bersch (Adult Education Research Conference, 2012)
In the early years of the field of adult education in the United States, women were prominent contributors to the growth of the field, particularly to the literature base. Previous publications provide some explanation for why women moved from the center to the margins as contributors to the field‘s literature base after the early period, but no extended analysis of the early women contributors has been conducted. This research project is designed to address that gap. The initial phase of the project, reported during a 2008 AERC Roundtable, examined the roles of women in developing the literature base from 1926-1941, the types of literature produced, and the connections or networks that may have fostered their efforts. The initial work investigated the Journal of Adult Education; and the series Studies in the Social Significance of Adult Education in the United States, both published by the American Adult Education Association (AAEA). It also identified some of the connections among many of the women.
Keywords: Women adult educators; Journal of Adult Education; history